KEPUTUSAN PEMBELIAN ONLINE KONSUMEN SHOPEE DAN FAKTOR YANG MEMPENGARUHI - Wafrotur Rohmah (Program Studi Manajemen, 2021)
The purpose of this study is to determine the effect of trust, convenience and quality of information on shopee consumers' online purchasing decisions. This study uses four variables, namely trust, convenience, quality of information and purchasing decisions. The research sample is students in Yogyakarta who are consumers of the shopee online buying and selling site. The data analysis tool uses Multiple Linear Regression Analysis. The results of the analysis show that (1) Trust, convenience and quality of information simultaneously have a significant effect on Online Purchase Decisions on the Shopee Online Buying Site. (2) Partially trust has a significant positive effect on Online Purchase Decisions on Shopee Online Buying Sites (3) Partially convenience has a significant positive effect on Online Purchase Decisions on Shopee Online Buying Sites and (3) Partially the quality of information has a significant positive effect on Online Purchase Decisions on the Shopee Online Buying Site.